The Use of a Three Dimensional Pop Up Book to Improve Reading Skills among Students at Nur Al-Islam Islamic Elementary School Rempoa - Falih Atabik, Muhammad; Mukhson Nawawi; Muhbib Abdul Wahab (INTIFA: Journal of Education and Language, 2026)
This study aims to identify the effectiveness of using the Pop-Up Book in improving the reading skills of fourth-grade students at MI Nurul Islam Rempoa. The researcher employed a quantitative method with a quasi-experimental design by administering pre-tests and post-tests to two groups: an experimental group that studied using the Pop-Up Book, and a control group that was taught using the audio-lingual method. The results showed a significant increase in the average score of the experimental group from 57.88 in the pre-test to 91.53 in the post-test, while the average score of the control group increased from 53.95 to only 74.17. The Mann–Whitney test also revealed statistical significance at the level of p = 0.00, indicating a substantial difference between the two groups in favor of the experimental group. The N-Gain coefficient reached 82.97%, which is considered a high level, indicating strong effectiveness. These results indicate that the Pop-Up Book is an effective and appropriate educational medium for improving Arabic reading skills.   مستخلص البحث يهدف هذا البحث إلى الكشف عن فعالية استخدام وسيلة الكتاب ذي ثلاثة الأبعاد Pop Up Book في ترقية مهارة القراءة باللغة العربية لدى تلاميذ الصف الرابع في مدرسة نور الإسلام الابتدائية الإسلامية ريمبووا. وقد استخدم الباحث المنهج الكمي بتصميم شبه تجريبي، حيث شملت العينة مجموعتين: مجموعة تجريبية درست باستخدام الكتاب ذي الأبعاد الثلاثة، ومجموعة ضابطة درست باستخدام الطريقة السمعية الشفوية. وتم جمع البيانات من خلال الاختبار القبلي والاختبار البعدي لقياس تحصيل التلاميذ في مهارة القراءة. وأظهرت النتائج أن متوسط درجات المجموعة التجريبية ارتفع من 57,88 في الاختبار القبلي إلى 91,53 في الاختبار البعدي، في حين ارتفع متوسط درجات المجموعة الضابطة من 53,95 إلى 74,17 فقط. كما بيّن اختبار مان–ويتني وجود فروق دالة إحصائيًا عند مستوى (p = 0.00) لصالح المجموعة التجريبية. وبلغت قيمة معامل N-Gain نسبة 82,97%، وهي ضمن الفئة المرتفعة. وتشير هذه النتائج إلى أن الكتاب ذي الأبعاد الثلاثة وسيلة تعليمية فعّالة ومناسبة في تعليم مهارة القراءة باللغة العربية في المرحلة الابتدائية، كما تسهم هذه الدراسة إسهامًا عمليًا في توجيه المعلمين والمؤسسات التعليمية إلى توظيف هذه الوسيلة لزيادة دافعية التلاميذ وتحسين نتائج تعلمهم.